A fixed frequency PWM induction shower using the duty cycle - Sanajit, N.; Jangwanitlert, A. (My University, 2010)
This paper presents a 2 kW, 36.5 kHz induction shower using a duty cycle control. The principle of this depends on induction heating from high frequency electromagnetic induction. The high frequency electric current passes through two induction coils connected in parallel so as to induce current at work piece that uses a stainless steel box and transfer heat to water inside it. The control uses the duty cycle which is generated from integrated circuit. In addition, this paper analysis output power and efficiency compared with the duty cycle. The results waveform shown as a ZVS condition is agreed with the theory one. A fixed PWM induction shower gives the rated output power and makes the temperature rise to 41 °C at the work piece in steady state within 2 min. ©2010 IEEE.
Keywords: High frequency inverter; Induction shower